FACTORS PREDICTING PERCEIVED SELF-EFFICACY IN EMERGENCY MANAGEMENT AMONG PEOPLE AT RISK OF STROKE IN UBON RATCHATHANI PROVINCE - Chaisongmuang, Penpuk; Maninet, Surachai; Chananin, Yommana; Boonchuwong, Orathai (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2025)
This study aimed to investigate the factors predicting perceived self-efficacy in emergency management among people at risk of stroke. The sample consisted of 167 individuals diagnosed with hypertension, diabetes mellitus, hyperlipidemia, ischemic heart disease, or atrial fibrillation, who received services at subdistrict health-promoting hospitals in Ubon Ratchathani Province. Participants were selected using simple random sampling. The research instruments included questionnaires on self-management, health literacy, social support, stress, and perceived self-efficacy in emergency management. All instruments were reviewed for content validity by a panel of experts. Cronbach’s alpha coefficients were .714, .917, .793, .706, and .805, respectively. Data were analyzed using descriptive statistics, Pearson’s correlation coefficient, and stepwise multiple linear regression analysis. The results showed that the participants had a moderate level of perceived self-efficacy in emergency management (M = 30.87, SD = 6.08). Social support, health literacy, self-management, and stress were significantly correlated with perceived self-efficacy in emergency management. Among these, only social support and health literacy were significant predictors, together explaining 31.5% of the variance in perceived self-efficacy in emergency management. Therefore, promoting health literacy and social support among individuals at risk of stroke may help improve their perceived self-efficacy in managing emergencies.